Preparação e caracterização de pós e filmes finos cerãmicos de titanato de chumbo e estrôncio obtidos por método químico - Leal, Sérgio Henrique Bezerra de Sousa (2006)
xvii ABSTRACT In this work it is approached the preparation of ceramic powders and thin films of strontium-doped lead titanate with concentration of strontium varing from 0 to 100% mol, using a chemical method of synthesis, polymeric precursor method (Pechini). This method allows the sythesis in aqueous medium, in ambient atmosphere, using reactants easily available. In this way, the synthesis condicions were optimized in order to elimanate the formation of secondary phases. The powders ceramic treated in different temperatures under ambient atmosphere was studied by differential scanning calorimetry (DSC), X-ray diffraction (XRD), infrared spectroscopy (FTIR), micro-Raman spectroscopy, scanning electron microscopy (SEM) and transmission electron microscopy (TEM), that allowed the identification of the crystalline phases, lattice parameters and crystallite size. A phase transition from tetragonal to cubic was observed in this system as the stontium concentration increases in the (Pb1-xSrx)TiO3. A pseudo-cubic phase was observed for x=0.5, indicanting the complete solid solubility of the system. Thin films were obtained by using spin coating of the polymeric solution on Pt/Ti/SiO2/Si substrates using a rotation speed of 7600 rpm for 30 s and calcining at 600°C for 4 h. The effect of the substituint ion in the microstructure and morphology of those films was discussed through a systematic and detailed study using XRD, FTIR, micro-Raman spectroscopy, optical microscopy and atomic force microscopy (AFM); where it was verified that addition of strontium in the PT lattice resulted in decrease of avarage grain size of those films.